Morphology of the Cervical Lymph Nodes of Agouti (Dasyprocta prymnolopha, Wagler, 1831) - de Carvalho, Paulo Gustavo Sedenho; Guerra, Sérgio Paulo Lima; Rizzo, Márcia dos Santos; da Silva, Andrezza Braga Soares; Cavalcante, Maria Michele Araújo de Sousa; Conde Júnior, Airton Mendes (Journal of Morphological Sciences, 2018)
In the scientific literature, works related to the morphology and histology of agoutis, Dasyprocta prymnolopha, Wagler, 1831, approach several organs and systems. However, none referenced the lymph nodes of this animal. The objectives of the present study were to perform morphological and histological analyses, under optical microscopy, of the cranial and cervical lymph nodes of agoutis, comparing them with the typical lymph nodes of already documented animal species. In the present work, four animals were used, respecting all the ethical and legal aspects, followed by the development of methodologies related to the morphology and histology in question. The results obtained did not show significant morphological and histological differences between the cranial and cervical lymph nodes of agoutis when compared with typical lymph nodes of the animal kingdom.
Keywords: lymph nodes; agouti; rodent; dasyprocta prymnolopha; histology